Enhanced near-infrared emission in Yb3+-Cr3+ codoped KZnF3 glass ceramics excited by a solar simulator. Issue 6 (15th April 2019) - Wang, Xin; Li, Wenhao; Tian, Ke; Lewis, Elfed; Wang, Shunbin; Brambilla, Gilberto; Dong, Yongkang; Wu, Xiao; Wang, Pengfei
Abstract: Cr 3+ -Yb 3+ codoped bulk glass-ceramics containing KZnF3 nanocrystals are fabricated by thermal treatment of cast glass samples and characterized by X-ray diffraction and transmission electron microscopy. The luminescent properties of the glass and glass ceramic are investigated from the measured photoluminescence spectra and fluorescent lifetime. The measurement results demonstrate that Cr 3+ and Yb 3+ ions are both predominantly hosted in the KZnF3 nanocrystals, and the energy absorbed by Cr 3+ ions is efficiently transferred to Yb 3+ ions when excited at 450 nm. Compared to the glass, the near-infrared emission in the Cr 3+ -Yb 3+ codoped glass ceramics is significantly enhanced when the excitation wavelength lies in the range λ~400–800 nm of a solar simulator. Results indicate that the Cr 3+ -Yb 3+ codoped KZnF3 glass ceramic provides a promising material for spectral conversion from visible sunlight to near-infrared emission and a novel gain material for solar pumped fiber laser.